PROFIL WANITA DAN PRIA DEWASA AWAL BELUM MENIKAH (STUDI DI KECAMATAN RANAH PESISIR) - Sefriani, Lidia; Hasan, Marwisni; Yusnetti, Yusnetti (Bimbingan dan Konseling, 2013)
The problems in this research based on phenomena that researcher found in the field. Preliminary female and male adult do not want to marriage. because they were enjoying with sufficient individual live. Focus on this research was 1) the reason of preliminary female adult does not want to getting marriage. 2) The reason of preliminary male adult does not want to get marriage. 3) Problems that preliminary female stay alone. 4) Problems that preliminary male adult still alone. Kind of this research was qualitative research which use study case. It means that, this research try to express in accurate and intend background of the preliminary female and male adult do not marriage. Technique of data analysis that used was narrative analysis. Informants in this research were 2 people. They are a female and male adult, they were parents, brother, sister, and friends. The result of this research described that 1) the preliminary female adult still alone because they wonât to be responsible to take care child and husband. 2) the preliminary male adult still aloneÂ  because they felt stress. 3) the preliminary female do not marriage yet because tempted by people around lonely woman. 4) felling sad because still a lonely.